Investigating omega-3 fatty acids’ neuroprotective effects in repetitive subconcussive neural injury: Study protocol for a randomized placebo-controlled trial - Lauren H. Beauregard; Jeffrey J. Bazarian; Blair D. Johnson; Hu Cheng; Gage Ellis; William Kronenberger; Philip C. Calder; Zhongxue Chen; Patricia Silveyra; Patrick D. Quinn; Sharlene D. Newman; Timothy D. Mickleborough; et al. (PLoS ONE, 2025)
Soccer (football) is the most popular sport globally, with 265 million players across all ages and sexes. Repetitive subconcussive head impacts due to heading of the soccer ball can pose threats to healthy brain development and aging. Omega-3 fatty acids, especially docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), may have neuroprotective effects, but it remains unclear what aspects of neural health benefit from DHA+EPA when faced with subconcussive head impacts. In a randomized placebo-controlled trial, 208 soccer players will complete baseline measures including demographics, blood sampling, dietary recalls, and psychological assessment. Participants will be randomly assigned to ingest DHA+EPA [3.4g/d: DHA 2.4g+EPA 1.0g] or placebo daily for 8 weeks followed by a subconcussion intervention phase. During the subconcussion intervention, participants will perform a session of 20 controlled soccer headings, with a second session 24 hours later. Blood samples, neuroimaging data, autonomic reactivity, and clinical measures (symptoms, oculomotor, cognition) will be collected pre-heading and 24-hour post-1st session, 24-hour post-2nd session, and 7-day post-2nd session. The primary hypothesis is that DHA+EPA pretreatment will promote neuronal and astrocyte resiliency to subconcussive head impacts, as assessed by blood biomarkers of brain injury, axonal microstructure measured by diffusion tensor imaging, and whole-brain resting-state connectivity. It is proposed that pretreatment will preserve autonomic function, as assessed by the cold pressor test (CPT), as well as oculomotor and cognitive function, even after head impacts. Data from this trial will help clarify the combined effect of DHA+EPA on brain molecular, cellular, and physiological health in response to subconcussive head impacts. If the hypotheses are confirmed, the findings will support a highly practical intervention for mitigating the neurodegenerative cascade triggered by head impacts. Trial registration: ClinicalTrials.gov NCT06736925